Species composition and interspecific association of plants in primary succession of Mount Merapi, Indonesia - SUTOMO SUTOMO; DINI FARDILA; LILY SURAYYA EKA PUTRI (Biodiversitas Journal of Biological Diversity, 2011)
Sutomo, Faradila D, Putri LSE (2011) Species composition and interspecific association of plants in primary succession of Mount Merapi, Indonesia. Biodiversitas 12: 212-217. Primary succession refers to the establishment of plant species and subsequent changes in composition following major disturbance such as volcanic activity. The study of succession may assist in recognizing the possible effects of species interactions (i.e. facilitation or inhibition). The barren landscapes created by volcanic disturbance on Mount Merapi, Java, Indonesia, provide excellent opportunities to study primary succession. Fifty-six species belonging to 26 families were recorded in the five nuÃ©es ardentes deposits. The highest number of species belonged to the Asteraceae, then Poaceae, followed by Fabaceae andRubiaceae. In Mount Merapi primary succession, the ecosystem may be developing with time as indicated by the increase in the number of species associations. The number of positive associations was generally higher than the number of negative associations, except in the 2001 deposit where it was equal. Native and alien invasive species had different patterns of interspecific associations. This research demonstrates that in primary succession sites on Mount Merapi, positive interspecific association increased as time progressed, which may support the view that facilitation is more prominent in a severely disturbed habitat as compared to competition.